Meloxiam as corrosion inhibitor for Aluminum in acid media Experimental and theoretical study - Haider A. Abood (University of Thi-Qar Journal of Science, 2019)
The effects of Meloxiam drug (MEL) on the corrosion of pure aluminum in 2 M HCl have beeninvestigated using weight loss methods. The measurement showed that the inhibition efficiencyincreased with increase in the concentration of inhibitor. The adsorption of the inhibitors on thealuminum surface obeyed Langmuir adsorption isotherm and had a physical mechanism. The effectof temperature on the corrosion behavior in the presence of different concentration of the MELinhibitors was studied in the temperature range of 25–65 °C. The associated activation energy ofcorrosion Ea and other thermodynamic parameters such as ΔH0ads ,ΔS0ads , (Kads) and ΔG0 ads were calculated to elaborate the mechanism of corrosion inhibition. Quantum chemical parameter such asHOMO,LUOM and Mulliken charge etc. have been calculated using DFT (B3LYP/ 6-311++G(d,p)),The results indicate that N and S atoms in the MEL structure was not effected in theadsorption of drug on the Al surface .